Capacitação de agricultores familiares para a produção de adubo orgânico e defensivos naturais na comunidade de Camurituba-Beira, no município de Abaetetuba – PA - GARCIA, Waldilene do Carmo (Universidade Federal do Pará, 2020)
The present work, carried out with a group of small farmers of the community of Camurituba- Beira, in the municipality of Abaetetuba - PA, aims to verify the economic viability of the production of organic fertilizer in quantity and quality adequate to increase and diversify the agricultural production, aiming local economic development. As a methodological procedure, interviews were, initially, made with the farmers participating in the project, to determine the characteristics of the productive areas and the main difficulties faced to ensure economic survival. In the second stage three theoretical and practical workshops were carried out to produce three types of fertilizer with different organic residues that are tested in the different crops, to verify the quality and quantity of fertilizer needed to increase their productivity. After tests of the different types of fertilizer, a cost-benefit balance is carried out and an agroecological data sheet is constructed in order to show step-by-step the procedures and techniques of organic fertilizer production to encourage small farmers to adopt these techniques to increase the productivity of their crops. At the farmers' request, a last workshop, on the possibilities of using not only organic fertilizer but also natural pesticides to verify the possibility of gradually migrating to agricultural production that can be considered organic has been realized. The workshop was of interest to several farmers who expressed their intention to try step by step to produce organic products and to test the economic viability.